Perencanaan Strategis Sistem Informasi Menggunakan Metode Tozer (Studi Kasus : CV. XYZ) - Cornellius Albert Handoyo (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Strategic planning Information systems are the right steps to be taken by companies in utilizing their business in the future. Cv. XYZ is a business entity engaged in chicken farming, focusing on egg production. This company already has an information system in the utilization of its business, but it is considered less than optimal because it does not cover all needs, especially in the field of taxation. This study uses the Tozer method to produce strategic planning information systems that can answer and support the needs of business processes in Cv. XYZ because this method can produce an analysis that covers their needs using easy and practical tools. The results of this research are in the form of application recommendations needed by companies to be more organized in data management and also recommendations for the C1000 application which will later include corporate taxation. This research is very important for companies to find out their business development in the next few years.